2017
DOI: 10.25115/odisea.v0i10.179
|View full text |Cite
|
Sign up to set email alerts
|

Tarnished Stars: The Discourses of Celebrity in the British Tabloid Press

Abstract: En este estudio se analiza el discurso referido a las celebridades en la prensa popular inglesa. El análisis se centra en los recursos lingüísticos utilizados en este contexto, y el discurso informal que se emplea para atraer y representar a los lectores. Se procede a un estudio crítico de las posiciones de sujeto ofrecidas al lector, y las relaciones retóricas que se establecen. En las conclusiones se subraya la función de la prensa popular como mediador social, irreverente sin ser amenazador, que genera disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…From a linguistic perspective, few studies focused on celebrity gossip that aims to promote interest in celebrities and reinforce their stardom in the minds of a mass audience. Breeze (2009), for example, reported that the discourse of celebrity gossip in the British tabloid, The Sun, employed several rhetorical and linguistic tools like the creation of identity chains, where the celebrity was referred to several times across a text using different yet co-referential elements. Members of an identity chain usually contained heavy noun phrases like "the self-styled king of pop", which serve as an "agenda-setting device which collapsed debatable issues into uncontested information bites" (Breeze, 2009, p. 10).…”
Section: Past Studies On Celebrity Worshipmentioning
confidence: 99%
See 1 more Smart Citation
“…From a linguistic perspective, few studies focused on celebrity gossip that aims to promote interest in celebrities and reinforce their stardom in the minds of a mass audience. Breeze (2009), for example, reported that the discourse of celebrity gossip in the British tabloid, The Sun, employed several rhetorical and linguistic tools like the creation of identity chains, where the celebrity was referred to several times across a text using different yet co-referential elements. Members of an identity chain usually contained heavy noun phrases like "the self-styled king of pop", which serve as an "agenda-setting device which collapsed debatable issues into uncontested information bites" (Breeze, 2009, p. 10).…”
Section: Past Studies On Celebrity Worshipmentioning
confidence: 99%
“…as endearingly cheered by his fans and the then 35 Goals, an indication of his (then) achievements. Duplicating Salah's image creates an identity chain with two (visual) elements referring to the same person, which has been argued to be characteristic of the rhetoric of glamour and a tool of textual cohesion (Breeze, 2009; see Section 4.2). However, in Figure 9 The two cartoons in Figure 11 share the common theme of contrasting Salah's performance with Liverpool on the one hand with his performance with the ENT on the other.…”
Section: Worshiped Kingsmentioning
confidence: 99%
“…Breeze (2009) เสนอบทความวิ จั ยเรื ่ อง Tarnished Stars: The Discourses of Celebrity in The British Tabloid Press โดยมุ ่ งศึ กษาวาทกรรมข่ าวของบุ คคลที ่ มี ชื ่ อเสี ยงใน หนั งสื อพิ มพ์ รายวั นขนาดเล็ กที ่ มุ ่ งเน้ นการน าเสนอข่ าวอื ้ อฉาว (tabloid) ในสหราชอาณาจั กร กลุ ่ ม ข้ อมู ลที ่ ใช้ ศึ กษาคื อ หนั งสื อพิ มพ์ The Sun มี กลุ ่ มเป้ าหมายเป็ นผู ้ อ่ านที ่ มี ก าลั งซื ้ อต่ า (Down หรื อเป็ นผู ้ ที ่ ใช้ ชี วิ ตอย่ างอภิ รมย์ เพราะร่ ารวย (great wastrels) อย่ างเป็ น เรื ่ องปกติ ในทางตรงกั นข้ าม หากดาราคนใดตกเป็ นข่ าวอื ้ อฉาว นั กหนั งสื อพิ มพ์ มั กจะแฝงการ ใช้ น้ าเสี ยงแบบภาษาปาก หรื อค าสแลงในการน าเสนอข่ าวนั ้ นๆ เช่ น "... Victoria Beckham is an airhead…”
unclassified